A GIS-based, microscale walkability assessment integrating the local topography. (July 2022) - Rahman, Ashikur
Abstract: This research sets an example of how large-scale walkability indices can be transformed into microscale walkability indices through a systematic evaluation of the different local components of the built environment. A Geographic Information System (GIS)-based qualitative scoring system of 15 micro-variables is developed to assess the walkability performances of the urban streets. Furthermore, the proposed microscale walkability index has been validated against real-world pedestrian surveys. The study also devises a method of quantifying the topographic variation within the catchments of urban streets and eventually, estimating its adverse impact on walkability. The City of Sydney area of Sydney, Australia is selected as the case study for its varying topography and availability of relevant data. The research is the first of its kind for incorporating the distinctive topography of Australian urban areas in the analysis of microscale walkability. Highlights: The microscale walkability index may act as an effective decision support system. The use of GIS may increase the time and cost-efficiency of walkability assessment. Walkability and varying topography are inversely related. The number of terrain contour lines and the catchment sizes are two prime determinants of topographic variation.